Not Yet Nirvana: International Higher Education Implications of the US Election - Altbach, Philip G.; de Wit, Hans (International Higher Education, 2021)
The departure of Donald Trump as president of the United States will bring some immediate and positive changes to the US and international higher education landscape. But the kind of populism and nationalism that Trump exemplified remains part of the US reality—and of the realities of many other countries. At best, one can say that international higher education will be in a less deplorable state under Biden, and that is something to be pleased about.